Teachers' Perceptions of Implementing the Constructivist Approach: A Case Study of One New Generation School in Phnom Penh, Cambodia - Vibol Onn; Kuen Im (Journal of Education Research, 2026)
This research study explored teachers’ perceptions of implementing the constructivist approach and the challenges they faced in applying constructivist learning in the classroom. A qualitative research design was employed, using purposive sampling, with critical case sampling applied to select ten moral and civic subject teachers as participants. Data were collected through semi-structured interviews, which were recorded, transcribed, and analysed using a colour-coding technique to extract key themes. The findings indicated that teachers generally held positive perceptions of constructivist learning within the New Generation School program, recognising its benefits for both teaching and learning. Constructivist educational theory was viewed as advantageous in promoting active learning, student engagement, and critical thinking. However, teachers also encountered challenges in its implementation, such as classroom management and adapting resources. Despite these difficulties, participants demonstrated a strong willingness to apply constructivist approaches and suggested practical solutions. Support from schools, colleagues, and stakeholders served as a motivating force in sustaining the implementation process.